2004
DOI: 10.1001/archotol.130.1.78
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Dehydrogenase 3 Genotype as a Risk Factor for Upper Aerodigestive Tract Cancers

Abstract: Objective: To assess alcohol dehydrogenase 3 (ADH3) polymorphism at position Ile349Val as indicator of risk factor for upper aerodigestive tract (UADT) cancer to verify its association with UADT cancer in nonalcoholic or nonsmoking individuals.Design: Cross-sectional study.Setting: Primary care or referral center. Patients:The study group consisted of 141 consecutive patients with newly diagnosed squamous cell carcinoma of the oral cavity, oropharynx, hypopharynx, or larynx admitted for surgical treatment. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 21 publications
0
10
0
4
Order By: Relevance
“…A single study in Brazil demonstrated elevated odds (OR 3.7, 95% CI, 1.5-9.7) of all head and neck squamous cell carcinomas (HNSCC; inclusive of oral cavity, oropharynx, larynx, and hypopharynx) for the homozygous ADH1C*1-1 genotype at low levels of alcohol consumption compared with the ADH1C*1-2 and ADH1C*2-2 genotypes. 58 Elevated odds (OR 5.3, 95% CI, 1.0-28.8) of oral cancer in association with the ADH1C*1-1 genotype were observed only among heavy alcohol users (57 drinks per week) in Puerto Rico 59 and among alcoholics in Germany 60 and France. 55,61 However, contradictory conclusions were reported in studies conducted in the U.S. 62,63 and Greece, 64 in which the ''slow metabolizing'' ADH1C*2-2 genotype was associated with increased risk for HNSCC among heavy drinkers.…”
Section: Alcohol Consumption and Metabolismmentioning
confidence: 99%
“…A single study in Brazil demonstrated elevated odds (OR 3.7, 95% CI, 1.5-9.7) of all head and neck squamous cell carcinomas (HNSCC; inclusive of oral cavity, oropharynx, larynx, and hypopharynx) for the homozygous ADH1C*1-1 genotype at low levels of alcohol consumption compared with the ADH1C*1-2 and ADH1C*2-2 genotypes. 58 Elevated odds (OR 5.3, 95% CI, 1.0-28.8) of oral cancer in association with the ADH1C*1-1 genotype were observed only among heavy alcohol users (57 drinks per week) in Puerto Rico 59 and among alcoholics in Germany 60 and France. 55,61 However, contradictory conclusions were reported in studies conducted in the U.S. 62,63 and Greece, 64 in which the ''slow metabolizing'' ADH1C*2-2 genotype was associated with increased risk for HNSCC among heavy drinkers.…”
Section: Alcohol Consumption and Metabolismmentioning
confidence: 99%
“…In contrast to ADH2, ADH3 is highly polymorphic in Caucasians. Of the 2 allelic variants, the ADH3*1 allele is associated with higher enzyme activity than the ADH3*2 allele and occurs in Caucasians at frequencies of 55-63% (253).In 5 (43,58,111-113) of 8 (63%) studies (43,58,(111)(112)(113)(114)(115)(116), ADH3*2/*1 heterozygotes showed decreased risk for HNC compared with *2/*2 homozygotes. However, in 6 (43,58, INTERNATIONAL JOURNAL OF ONCOLOGY 32: 945-973, 2008 …”
mentioning
confidence: 99%
“…[22][23][24][25] Çalışmamızda CCND1 G870A polimorfizmi incelendiğinde, baş-boyun kanserli hastalar ile kontrol grubu arasında risk alleli olarak kabul edilen A allelinin dağılımı açısından önemli bir fark gözlenmemiştir. Hasta ve kontrol grupları arasında genotip ve allel dağılımları açısından fark bulunmaması mide kanseri, 26 hepatosellüler kanser, 22 üst solunum ve sindirim sisteminin yassı epitel hücreli kanserleri, 27 hipofiz adenomu, 15 34 hastalarda kombine GA+AA genotipi artmış hastalık riskiyle ilişkili bulunurken, larinks 21 kanserinde hem GA genotipi, hem de kombine GA + AA genotipi artmış hastalık riskiyle ilişkilendirilmiştir.…”
Section: Discussionunclassified
“…Literatürde sigara kullananlarda nazofarinks 18 ve özofagus kanserinde, 34 sigara kullanmayanlar da ise mesane 19 ve baş-boyun kanserinde 12 A alleli ile hastalık riski arasında ilişki bildirilmektedir. Ayrıca üst aerodigestive sistemin alkol kullanmayan yassı epitel kanserli hastalarında 27 da A alleli risk faktörü olarak bildirilmiş ve 50 yaş altı veya kadın baş-boyun kanserli hastalarda aynı allele bağlı olarak üç kat artmış hastalık riski gözlenmiştir. 12 A allelinin mesane 33 ve serviks 30 kanserinde etnik köken (Asyalılarda daha sık) ve risk ile ilişkili olduğu bildirilmiştir.…”
Section: Ccnd1 (G870a)unclassified
See 1 more Smart Citation